A cross-sectional study on the cardiovascular risk associated with the Covid-19 Lockdown - Mathangi Murali; Sanathanan. N.Rs; Arbind Kumar Choudhary; A Abdul Rahman; L Madhan; E. Manivannan; R. Sivaraj (Innovative Journal of Medical and Health Sciences, 2021)
Background: In December 2019, an outbreak of Severe Acute Respi-ratory Syndrome Coronavirus-2 (SARS-CoV 2), emerged in Wuhan, China causing a global pandemic. Stringent measures were imple-mented in several parts of the world and a nation-wide lockdown was declared in India to alleviate disease transmission. This confinement severely impacted people’s lives and forced them to switch to a seden-tary lifestyle. The present study aimed to analyse the cardiovascular risk associated with lifestyle modifications due to the lockdown. Results :This cross-sectional study used a structured online questionnaire with data collection using convenience sampling method. The data analysis was performed using PASW Statistics Version 18.0.A total of 432 respondents, aged between 20 and 60 years (mean age-33.39 10.8 years) were included in the study. The perception of weight gain was observed in 46.06% of the population;19.90% reported an increased carbohydrate intake; a decrease in physical activity was observed in 27.08%; 62.73% reported an increase in screen time; more females complained of having sleep disturbances and stress perception was more in the population group aged between 30-50 years. Discussion: The behavioral and lifestyle risk factors of cardiovascular diseases are obesity, physical inactivity, sedentary behavior, and stress.7 Among the respondents, 46.06% have gained weight with the lockdown and this is evident from the increase in carbohydrate consumption in 28.64%and decreased physical activity in 34.67% of them. Based on previous studies, it can be speculated that the weight gained may not be easily reversed and may lead to excess adiposity which in turn can increase the cardiovascular risk. Conclusion: Quarantine results in an increased cardiovascular risk due to the associated unhealthy lifestyle and stress. Following quarantine, a global action supporting healthy diet and physical activity should be made mandatory to encourage people to return to a good lifestyle routine. This study would help in execution of public health interventions during the pandemic as well as in future times. Keywords: COVID-19, Sedentary lifestyle,Quarantine,Lifestyle, Cardiovascular diseases